THE ROLE OF THE NURSE IN THE COVID 19 DIAGNOSTIC PROCESS THROUGH COMPUTERIZED TOMOGRAPHY EXAMINATION - Regina Souza de Oliveira, Gessica; de Oliveira Matos, Luciana; Queiroz Pelegrineli, Samuel (Health and Society, 2023)
Introduction: this study takes as its object, computed tomography and the role of nurses who work at the Diagnostic Imaging Center, in patients with suspected Covid19. The general objective of the study was to know the role of the nurse who works at the Diagnostic Imaging Center in the Covid19 diagnostic process by CT scan. Specific objective focused on the characterization of the nursing work process in Computed Tomography in the Covid19 diagnosis process; as well as the performance of nurses in the complexity of care in CT scans, where the aim is to know the findings of CT scans in patients with COVID-19; and knowledge of the Nurse’s role in the imaging sector. Method: bibliographical research, in which an electronic search was carried out from the Virtual Health Library. Selecting the periodical publications of Brazilian nursing, found in the databases, MEDLINE, BDENF and LILACS. In a second moment, a questionnaire was elaborated on the role of the nurse during the anamnesis to perform the Computed Tomography in the process of diagnosing Covid19 (Appendix 1). In order to investigate the risk factors for the development of adverse reactions and provide safe venous access for the administration of the contraceptive, in addition to issues inherent in the Covid19 diagnostic process. Results: The analysis of the publications allowed us to understand and expand in a more qualified, safe and accessible way on the performance of nurses working in the Diagnostic Imaging Center for the evaluation of nurses in the Covid19 diagnosis process by CT scan. Conclusion: As it is a new topic and with few publications, it can contribute as a bibliographic reference for further research. In terms of assistance, it will help Imaging service nurses to favor their actions to combat COVID 19 and for individual and professional development, opening opportunities for new knowledge and reaffirming the power of nursing work.